University Management: Organizational Culture as a Factor of University Competitiveness - Habibi, Surya; Prasetyo, Muhammad Anggung Manumanoso (Development: Studies in Educational Management and Leadership, 2022)
This research examines the organizational culture at Islamic universities in Indonesia to gain an Islamic university competitiveness. The qualitative research method is used, with data gathered through interviews, observations, and documentation. According to the study's findings, the conceptual framework of organizational culture plays a role in increasing universities' competitive advantage. The study's findings highlight the organizational culture-building model and its framework (competing value framework). Furthermore, the study's findings highlight the need for a reorientation of vision, adaptation to technological renewal, development of partnership-based networks, and enhancing academic services. Multi-stakeholder networks are essential in mediating the relationship between organizational culture and university competitive advantage. This research's originality fills gaps in the literature on cultural studies and organizational behavior in higher education. Studies on organizational culture in creating competitive universities and organizational resilience are still limited.